Assessing the Feasibility of Developing a Menopause Clinic as a Specialized Flagship Service at MedicElle Primary Clinic, Surabaya - Nabil Salim Ambar; Ansarul Fahrudda; Solichul Absor (Universitas Muhammadiyah Surabaya, 2026)
Menopause represents a natural stage in a woman’s life that may be accompanied by physical, psychological, and social symptoms requiring appropriate clinical management. This study aimed to conduct a preliminary assessment of the feasibility of establishing a dedicated Menopause Clinic as a flagship service at MedicElle Primary Clinic in Surabaya. A quantitative descriptive study with a retrospective cross-sectional design was conducted using medical records of women aged 40-60 years who met the inclusion criteria. A total of 58 eligible participants were selected through a total sampling approach. The majority of participants were in the perimenopausal period and presented with multiple menopausal symptoms, predominantly vasomotor complaints, sleep disturbances, psychological manifestations, urogenital symptoms, and musculoskeletal pain. Overall, 82.7% of the patients experienced at least one menopausal symptom, with a mean Complaint Index of 2.8. Indicators of service readiness demonstrated the availability of six healthcare professionals, a facility readiness score of 4.2 out of 5, a follow-up rate of 67%, and a medical record completeness rate of 93%. These findings suggest that the institution has demonstrated preliminary readiness and that there is a clear demand for menopause related healthcare services. However, the overall feasibility of establishing the proposed clinic cannot yet be fully determined because important aspects, including financial feasibility, patient satisfaction, healthcare provider perspectives, and long-term clinical outcomes, were not evaluated in this study.